2018
DOI: 10.1186/s11671-018-2696-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Transition Metals on Black Phosphorene: a First-Principles Study

Abstract: Black phosphorene is a novel two-dimensional material which has unique properties and wide applications. Using first-principles calculations, we investigated the adsorption behavior of 12 different transition metals (TMs; Fe, Co, Ni, Cu, Ru, Rh, Pd, Ag, Os, Ir, Pt, and Au) on phosphorene. Our results showed that all of the adsorption systems have a large binding energy. The Fe-, Co-, and Au-phosphorene systems display magnetic states with magnetic moments of 2, 1, and 0.96 μB, respectively, which means that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 57 publications
1
23
1
Order By: Relevance
“…Ru and Ir atoms possess higher binding strengths ( E b (Ru)=−5.71 eV, E b (Ir)=−5.92 eV) on Pn than other metals, while Au−Pn shows the weakest strength ( E b (Au)=−1.86 eV). The binding strength of single metal atom on Pn decreases in the following order: Ir>Ru>Rh>Pt>Pd>Au, in accord with previous studies [76] . It can also be seen that strong binding M−Pn systems all have short M−P bond lengths.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Ru and Ir atoms possess higher binding strengths ( E b (Ru)=−5.71 eV, E b (Ir)=−5.92 eV) on Pn than other metals, while Au−Pn shows the weakest strength ( E b (Au)=−1.86 eV). The binding strength of single metal atom on Pn decreases in the following order: Ir>Ru>Rh>Pt>Pd>Au, in accord with previous studies [76] . It can also be seen that strong binding M−Pn systems all have short M−P bond lengths.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, single metal doped phosphorene feature excellent activity towards OER, ORR, hydrogen evolution reaction (HER) and nitrogen reduction reaction (NRR) [70–75] . Theoretical studies on binding of various transition metals on phosphorene and the adsorption behaviour of O 2 molecules on these doped systems indicate that they could present high stability and good catalytic activity for CO oxidation reaction due to the easily activated O−O bond, which may open new possibilities for catalytic applications [76] …”
Section: Introductionmentioning
confidence: 99%
“…[47,48] Three different possible sites were considered for the adsorption and interaction of gas molecules and metal atoms on the BP. [29,49] All the selected VOC gas molecules and metal were located at a distance of 2 Å above H, B, and T sites, where they are hollow hexagon, P─P bond, and top of P atom, respectively (exhibited in Figure 1a). The molecular axis of gas molecules is aligned parallel and perpendicular respecting the BP's plane.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of nanoscience, various types of nanostructures such as nanotubes, nanoplates, nanocones, and nanoforms have been greatly investigated as potential candidates in various fields such as drug delivery compounds [8][9][10][11][12], and it has been found that nanotubes and the nanocages are the most Preferred candidates for drug carriers due to their high sensitivity to drug particles, fewer side effects, hydrophobic properties, and unique spherical shape, etc. [13][14][15][16]. Lately, the interactions between nanotubes and ligands became an important issue, and they can be used together as drug delivery agents as well as sensors [17][18].…”
Section: Introductionmentioning
confidence: 99%